Development Of An Automated Inspection System For Welding Defect Detection. - Fong, Thai Koay; Chee, Peng Lim; Sundaram, Shanmuga (2007)
In industrial radiograph inspection, it is an important step to extract welding region from the radiograph image to avoid processing of complex background.